PENGARUH FIXED ASSET INTENSITY DAN GOVERNANSI KORPORAT TERHADAP PENGHINDARAN PAJAK - Tiara Prasetya Dhiyanti; Ibram Pinondang (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2026)
This study aims to examine and analyze the effect of fixed asset intensity and corporate governance on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The research method used is a quantitative method with a descriptive approach. The population in this study includes all energy sector companies listed on the IDX, with a sampling technique using purposive sampling, resulting in a total of 34 companies as the observation sample. The data analysis technique used is panel data regression analysis with the selection of the Random Effects Model (REM) processed using Eviews series 13 software. The results show that fixed asset intensity affects tax avoidance. This indicates that companies with large fixed asset holdings tend to have high depreciation expenses, where these non-cash expenses function as a tax shield that effectively reduces taxable income and the Effective Tax Rate (ETR). Meanwhile, the results of the study on corporate governance variables proxied by the frequency of independent board of commissioners meetings had no effect on tax avoidance. These findings suggest that the number of meetings held by the board of commissioners tends to be merely a formality to comply with Financial Services Authority (OJK) regulations and has not been able to demonstrate substantive oversight of corporate tax policies.